Risk Factors for Major Adverse Cardiovascular Events in Phase III and Long‐Term Extension Studies of Tofacitinib in Patients With Rheumatoid Arthritis. Issue 9 (6th August 2019) - Charles‐Schoeman, Christina; DeMasi, Ryan; Valdez, Hernan; Soma, Koshika; Hwang, Lie‐Ju; Boy, Mary G.; Biswas, Pinaki; McInnes, Iain B.
Abstract : Objective: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). This study was undertaken to evaluate the risk of major adverse cardiovascular events (MACE) in patients with RA receiving tofacitinib. Methods: Data were pooled from patients with moderately to severely active RA receiving ≥1 tofacitinib dose in 6 phase III and 2 long‐term extension studies over 7 years. MACE (myocardial infarction, stroke, cardiovascular death) were independently adjudicated. Cox regression models were used to evaluate associations between baseline variables and time to first MACE. Following 24 weeks of tofacitinib, changes in variables and time to future MACE were evaluated after adjusment for age, baseline values, and time‐varying tofacitinib dose. Hazard ratios and 95% confidence intervals were calculated. Results: Fifty‐two MACE occurred in 4, 076 patients over 12, 873 patient‐years of exposure (incidence rate 0.4 patients with events per 100 patient‐years). In univariable analyses of baseline variables, traditional cardiovascular risk factors and glucocorticoid and statin use were associated with MACE risk; disease activity and inflammation measures were not. In subsequent multivariable analyses, baseline age, hypertension, and the total cholesterol to high‐density lipoprotein (HDL) cholesterol ratio remained significantly associated with risk of MACE. After 24 weeks of treatment, an increase in HDL cholesterol and a decrease in the total to HDL cholesterol were associated with decreased MACE risk; changes in total cholesterol, low‐density lipoprotein (LDL) cholesterol, and disease activity measures were not. Increased erythrocyte sedimentation rates trended with increased future MACE risk. Conclusion: In this post hoc analysis, after 24 weeks of tofacitinib treatment, increased HDL cholesterol, but not increased LDL cholesterol or total cholesterol, appeared to be associated with lower future MACE risk. Further data are needed to test the cardiovascular safety of tofacitinib.